Gas Sensors Based on Nanostructures of Binary and Ternary Oxide Systems - S. S. Nalimova; V. A. Moshnikov; Z. V. Shomakhov; V. M. Kondratev (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Nanomaterials based on binary and multicomponent oxides are of interest for the development of catalysts, photocatalysts, gas sensors, solar cells, as well as in other fields. The most effective methods to produce oxide systems of various compositions are those of chemical co-deposition, as well as two-stage approaches.Aim. To develop sensor nanomaterials based on ZnO, Zn–Fe–O, and Zn–Sn–O ternary oxide nanosystems, as well as to develop methods for assessing their properties.Materials and methods. ZnO and ZnFe2O4 nanopowders were synthesized by chemical coprecipitation, and ZnFe2O4 and Zn2SnO4 nanostructures were produced by modifying ZnO nanowires. The surface chemical composition and microstructure were studied using scanning electron microscopy, backscattered electron diffraction, and Xray photoelectron spectroscopy. The sensor responses of the samples to vapors of organic solvents were analyzed.Results. The response value of zinc oxide and zinc ferrite samples synthesized by chemical coprecipitation was found to be 2–4 orders of magnitude higher than that of modified zinc oxide nanowires. The formation of ternary oxide nanostructures led to an increase in the sensor response of zinc oxide nanowires. This effect can be explained by the formation of adsorption sites of various types during formation of such systems. The samples produced by chemical coprecipitation showed an extremely high sensor response. This may be due to the formation of fractal structures at the percolation threshold.Conclusion. ZnO and ZnFe2O4 oxide nanostructures produced by chemical coprecipitation exhibit a high sensor response to acetone and ethanol vapors. Methods for the formation of multicomponent oxide systems with improved sensor properties compared to the original zinc oxide nanowires were developed. The resultant sensor nanomaterials are promising for use as sensitive layers of gas sensors for detecting organic solvent vapors.